2013
DOI: 10.4018/ijiit.2013100105
|View full text |Cite
|
Sign up to set email alerts
|

A Transaction-Oriented Architecture for Enterprise Systems

Abstract: Many enterprises risk business transactions based on information systems that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…This conceptual modeling grammar for the business domain overarches the supply chain and enterprise domains of business information systems and provides a conceptual basis for both information systems development and integration. The modeling grammar was committed 1 to the REA ontology because of REA's structuring orientation, which facilitates knowledge representation and interpretation by structuring knowledge in easily recognizable recurrent patterns (Dunn & McCarthy, 1997;Poels, Maes, Gailly, & Paemeleire, 2007;Polovina, 2013). The structuring orientation is one of the features of REA that has made it popular in several domains, including education, knowledge management and supply chain management (Gailly, Laurier, & Poels, 2008;Guido L. Geerts, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This conceptual modeling grammar for the business domain overarches the supply chain and enterprise domains of business information systems and provides a conceptual basis for both information systems development and integration. The modeling grammar was committed 1 to the REA ontology because of REA's structuring orientation, which facilitates knowledge representation and interpretation by structuring knowledge in easily recognizable recurrent patterns (Dunn & McCarthy, 1997;Poels, Maes, Gailly, & Paemeleire, 2007;Polovina, 2013). The structuring orientation is one of the features of REA that has made it popular in several domains, including education, knowledge management and supply chain management (Gailly, Laurier, & Poels, 2008;Guido L. Geerts, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To extend our understanding of SOEC Transactions, the EMPRISES framework incorporates the Transaction Concept from Transaction-Oriented Architecture (Polovina, 2013). The Transaction Concept, based on Resource-Events-Agents (REA) identifies the "real-world" agents in enterprise transactions, how they transact (the Events), and what they transact (the Resources) (Vymětal & Scheller, 2012;Laurier & Poels, 2014).…”
Section: The Soec Transaction Conceptmentioning
confidence: 99%
“…To benefit from these central integrated Information Systems (IS), organizations have spent billions of dollars on the implementation of ERP systems, whereby the objective has been to focus primarily on improving transaction handling through the standardization of business processes and integration of operations and data (Holsapple and Sena, 2005). SAP is one of the prevalent ERP system vendors and it is understood that 65-70% of the world's transactions involve SAP systems Forbes (LLC, 2011) quoted by Polovina (2013).…”
Section: Motivationmentioning
confidence: 99%
“…ERP systems must complete a multitude of repetitive and bespoke business transactions to fulfil the organisations goals. Several authors have shown previously, that storing the transactions using what could be called a TOA based on the REA ontology offers a theoretical solution to these problems and can be useful in capturing the semantics of ERP systems (Polovina, 2013;Launders, 2011;Fallon and Polovina, 2013).…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation